EXAMINING THE INFLUENCE OF ORGANIZATIONAL CLIMATE AND ATTITUDE TOWARD KNOWLEDGE SHARING ON KNOWLEDGE SHARING INTENTION - Rini Sarianti; Rahmiati Rahmiati (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2013)
This study investigated the influence of organizational climate and attitude toward knowledgesharing on knowledge sharing intention. The populations in this research are all administrativeemployees in Padang State University. Technique of sample analysis is proportional clustersampling. Data were collected through a questionnaire using Likert scale. Convergent anddiscriminative validity were used to test the validity and reliability of the questionnaire. Partialleast square (PLS) was chosen as the structural equation model (SEM) analysis methods to testthe hypotheses. The findings of the research are: (1) organizational climate has significanteffect on knowledge sharing intention, (2) organizational climate has significant effect onattitude toward knowledge sharing, and (3) attitude toward knowledge sharing has significanteffect on knowledge sharing intention.Penelitian ini meneliti pengaruh iklim organisasi dan sikap berbagi pengetahuan terhadap niatberbagi pengetahuan. Populasi dalam penelitian ini adalah karyawan administrasi diUniversitas Negeri Padang. Teknik pengambilan sampel menggunakan proportional clustersampling. Data dikumpulkan melalui kuesioner dengan menggunakan skala Likert. Konvergendan validitas diskriminatif digunakan untuk menguji validitas dan reliabilitas kuesioner.Kuadrat terkecil parsial (PLS) dipilih sebagai model persamaan struktural (SEM) untukmetode analisis pengujian hipotesis. Temuan dari penelitian ini adalah: (1) iklim organisasiberpengaruh signifikan terhadap niat berbagi pengetahuan, (2) iklim organisasi berpengaruhsignifikan terhadap sikap terhadap berbagi pengetahuan, dan (3) sikap berbagi pengetahuanberpengaruh signifikan terhadap niat berbagi pengetahuan.